Serotonin Gene Variants are Unlikely to Play a Significant Role in the Pathogenesis of the Sudden Infant Death Syndrome - Paterson, David S (2013)
Sudden infant death syndrome (SIDS) is defined as the sudden and unexpected death of an infant less than 12 months of age that is related to a sleep period and remains unexplained after a complete autopsy, death scene investigation, and review of the clinical history. The cause of SIDS is unknown, but a major subset of SIDS is proposed to result from abnormalities in serotonin (5-HT) and related neurotransmitters in regions of the lower brainstem that result in failure of protective homeostatic responses to life-threatening challenges during sleep. Multiple studies have implicated gene variants that affect different elements of 5-HT neurotransmission in the pathogenesis of these abnormalities in SIDS. In this review I discuss the data from these studies together with some new data correlating genotype with brainstem 5-HT neurochemistry in the same SIDS cases and conclude that these gene variants are unlikely to play a major role in the pathogenesis of the medullary 5-HT abnormalities observed in SIDS.